The Effect of Student Integrity on Academic Fraud: Dimensions of Fraud Pentagon Theory: (Case Study on Students at SMAN 2 AIKMEL) - Febriana, Widia; Anggriani, Rini; Aryani, R. Ayu Ida (Universitas Nusantara PGRI Kediri, 2023)
Research aim : This study was conducted to examine the effect of student integrity on the tendency of academic fraud to occur using the fraud pentagon perspective. Design/Method/Approach : This research was conducted at SMAN 2 Aikmel, East Lombok Regency, using primary data by distributing questionnaires to collect data and determine respondents based on non-probability sampling and purposive sampling. In accordance with the predetermined criteria, the questionnaire was given to students and students at SMAN 2 Aikel. The proposed hypothesis was tested using multiple regression analysis. Research Finding : The results showed that pentagon cheating had a positive effect on academic cheating, and student integrity had a negative effect on academic cheating. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : -